Relação do homem com a natureza no pensamento de João Amós Comenius - Heiderich, Carloman Cordovil (2011)
In recent years it comes growing the quarrel around the ambient questions. Test of this is in the fact of that the year of 2010 was declared, for the Organization of United Nations (ONU), the year of Biodiversity. As its official site is about a celebration of the life in the land and the valuation of the diversity of the life. In the reply the question how much at the rate of the ONU to have chosen the year of 2010, explicit one that the man is integrant part of the nature and has the power to protect it or to destroy it. The present research has as deep cloth of the reflection that involves the environment and the year of Biodiversity. Initially the intention was to use the term environment in the comeniano thought, however, for if dealing with a term of the current society, it was understood that more it would be adjusted, to discourse regarding the relation of the man with the nature, having as focus two workmanships of John Comenius: Great Didactics and Pampaedia. Therefore, it had as objective principal of the research to identify in the thought of John Comenius the relation of the man of the one with the nature. For in such a way, it was broken of the norteador principle of that John Comenius demonstrated in the Great Didactics and in its Pampaedia he had concern in waving for its world that an improper relation of the man with the nature, over all, when this of it if uses for exploratórios ends and incompatible with the purpose for which she was servant, it makes with that it suffers and with it the human being.